Odpowiedzi

Najlepsza Odpowiedź!
2010-02-06T20:28:11+01:00
A) -3x(-2x²-4x+1)-5(x³-3x+2)= 6x³+12x²-3x-5x³+15x-10= x³+12x²+12x-10

b)4(x³-2x²-5x+2)-x(2x²-3x+5)= 4x³-8x²-20x+8-2x³+3x²-5x= 2x³-5x²-25x= x(2x²-5x-25)

c)3(0,6a-1,1b+0,9c)-4(0,3a+1,2b-0,3c)= 1,8a-3,3b+2,7c-1,2a-4,8b+1,2c= 0,6a-8,1b+3,9c

d)(x²-6x+18):3+(x²-3x+5):2= ⅓x²-2x+6+½x²-1½x+2½= ⅚x²-3½x+8½

e)(10x²-5x+15):(-5)+(6-2x+3x²):2 = -2x²+x-3+3-x+1½x²= -½x²
2010-02-06T20:34:20+01:00
A) -3x(-2x²-4x+1)-5(x³-3x+2)=6x³+12x²-3x-5x³+15x-10=x³+12x²+12x-10

b)4(x³-2x²-5x+2)-x(2x²-3x+5)=4x³-8x²-20x+8-2x³+3x²-5x=2x³-5x²-25x+8

c) 3(0,6a-1,1b+0,9c)-4(0,3a+1,2b-0,3c)=1,8a-3,3b+2,7c-1,2a-4,8b+1,2c=0,6a-8,1b+3,9c

d) (x²-6x+18):3+(x²-3x+5):2=x²:3-2x+6+x²:2-3:2x+5:2=5x²:6-7:2x+17:2

2010-02-06T20:34:30+01:00
A)-3x(-2x²-4x+1)-5(x³-3x+2)=6x³+12x²-3x-5x³+15x-10=11x³-12x²+12x
b)4(x³-2x²-5x+2)-x(2x²-3x+5)=4x³+8x²+20x+8+2x³+3x³-5x=9x³+8x²+20x+8
c)3(0,6a-1,1b+0,9c)-4(0,3a+1,2b-0,3c)=1,8a-3,3b+2,7c-1,2a+4,8b+1,2c=0,6a+1,5b+3,9c

tylko tyle wiem;)